How Relevant is Targeting to the Success of an Antipoverty Program? - Ravallion, Martin (World Bank, Washington, DC, 2012)
Policy-oriented discussions often assume that "better targeting" implies larger impacts on poverty or more cost-effective interventions. The literature on the economics of targeting warns against that assumption, but evidence has been scarce. The paper begins with a critical review of the strengths and weaknesses of the targeting measures found in practice. It then exploits an unusually large micro data set for China to estimate aggregate and local-level poverty impacts of the country's main urban antipoverty program. Standard measures of targeting are found to be uninformative, or even deceptive, about impacts on poverty and cost-effectiveness in reducing poverty. In program design and evaluation, it would be better to focus directly on the program's outcomes for poor people than to rely on prevailing measures of targeting.